Análise econômica do mercado de pedras preciosas na região do Médio Alto Uruguai do estado do Rio Grande do Sul - Valle, Carine Dalla (2018)
Brazil is one of the highlights in mineral production, possessing in its territory a great quantity and variety of precious stones, being one of the traditional sectors of the Brazilian economy and that receives great international attention. In this sense, the extraction of precious stones has great relevance in the socioeconomic development of the regions next to the extraction and processing sites, providing resources and foreign exchange and leveraging the sector through the aggregation of value to the products traded. The present study of the precious stone production chain focuses on the extraction and commercialization analysis in the municipality of Ametista do Sul /RS, in the national and international scope, aiming to understand the role of innovation as a competitive advantage. For this, theories were used on Production Chains and Local Productive Arrangement (APL), New Institutional Economics (NEI) and Transaction Cost Economics (ECT), Marketing and International Market, Innovation, Innovation as a Strategy, and Competitiveness. The methodology used to obtain the research data was based on bibliographic research, qualitative-descriptive field research, whose data were obtained through informal visits, interviews and the application of questionnaires with the key agents representing the links of the productive chain of the precious stone. Thus, the results of the mapping of the process of extraction and characterization of the chain of production indicate that the chain links are the garimpeiros, lapping companies, processing industries, companies and / or agents of commercialization in the domestic market and export until reaching the consumer final, as well as all logistics and distribution during the process, verifying that there are problems of organization, control and inspection of the activity, which hinders the development and growth of the sector. In relation to the understanding of the institutional environment, the data reveal that there is a high level of informality throughout the process and the inadequate use of resources, the activity develops under conditions that depend on internal factors, such as bureaucratic processes, tax and tax burden. in the light of the NIS, the governance structures used according to the attributes and behavioral presuppositions between the transactions between garimpeiros, garimpos owners, stoning companies, beneficiation, sale and export, uncertainties occurring, limited rationality, specific assets in the transactions. International marketing and market data also show that around 95% of production is destined for the foreign market, mainly for Asian and American destinations, and the remaining 5% is in the Brazilian market. It is noteworthy that 80% of the precious stones extraction carried out in the municipality is sent to Soledade/RS for processing and industrialization, leading to losses in the aggregation of value. Finally, the results on innovation, it was visualized that tourism is considered a competitive factor in the regional, state and world scenario, being titled as "World Capital of the Amethyst Stone", being determinant for the economic and productive development of the chain. It is concluded that the productive chain of precious stones has great importance for the local and regional economy, consolidating itself as reference in the extraction of precious stones in crude form, seeking to increase the industrialization and the export of jewels, however, so that this it is necessary to formalize the transactions, better organization and control of the activity. According to this, the competitive differential is the strategies adopted to leverage the sector, such as innovation aligned with tourism, being the propeller of the economy and the productive chain of precious stones.